Optimised DNA isolation protocols for key arid and semi-arid fruit trees to enhance genetic improvement - Kiruba, M; Rajan Babu, V; Bhuvana, S; Mangammal, P; Kumar, P; Rajasekaran, R (Plant Science Today, 2026)
The study was conducted at Forest College & Research Institute, Mettupalayam, Tamil Nadu to optimize the DNA extraction protocols for important arid and semi-arid fruit trees. Arid and semi-arid fruit trees, including Emblica officinalis, Aegle marmelos, Ziziphus mauritiana, Buchanania lanzan and Carissa grandiflora, play a crucial role in India’s rural economy by providing nutritional security and supporting agroforestry systems. However, the availability of quality planting materials resilient to climate variability remains a big challenge. DNA analysis is a valuable tool for the genetic improvement of long-rotation tree species, aiding in the selection of high-yield and climate-resilient genotypes. Effective DNA extraction is essential for molecular studies but is hindered by the presence of high levels of polysaccharides, polyphenols and tannins. This study aimed to standardize species-specific DNA isolation protocols using three methods CTAB, modified CTAB and SDS. DNA yield and purity were assessed using a Thermo Scientific NanoDrop™ 1000 Spectrophotometer and agarose gel electrophoresis. The highest DNA yield for E. officinalis was obtained using the modified CTAB method (1074 ng/µL), while A. marmelos, B. lanzan and C. grandiflora showed optimal results with the CTAB method, yielding 508 ng/µL, 1106.6 ng/µL and 474 ng/µl, respectively. For Z. mauritiana, the SDS method was superior, yielding 1159.6 ng/µL with a purity ratio (A260/A280) of 1.6. These optimized protocols facilitate molecular breeding, stress-resistance screening and genetic enhancement of these vital species.